International Trends in Accreditation and Quality Assurance: Challenging Possibilities - Blanco, Gerardo; Bernasconi, Andrés (International Higher Education, 2025)
<h3 id="accreditation-has-emerged-as-the-most-widely-adopted-approach-to-ensuring-higher-education-quality-around-the-world-while-this-approach-allows-variations-it-provides-a-common-language-shared-by-different-systems-and-academic-traditions-while-cooperation-across-agencies-will-continue-to-intensify-the-future-presents-the-risk-of-undue-governmental-intervention" data-pm-slice="1 1 []">Accreditation has emerged as the most widely adopted approach to ensuring higher education quality around the world. While this approach allows variations, it provides a common language shared by different systems and academic traditions. While cooperation across agencies will continue to intensify, the future presents the risk of undue governmental intervention.